Allozyme variations of Trichoderma harzianum and its taxonomic implications - Siddiquee, Md. Shafiquzzaman; Abdullah, Faridah; Tan, Soon Guan; Leng, Min See (American-Eurasian Network for Scientific Information, 2007)
Electrophoretic variation of nine allozyme systems encoded by 14 gene loci were studied on 47 isolates from 3 species of Trichoderma namely, T. harzianum, T. aureoviride and T. longibrachiatum. Polyacrylamide gel electrophoresis was used to investigate the taxonomic circumscription of T. harzianum populations and to evaluate the levels of genetic variations and the population structure. The Level of genetic variations in T. harzianum populations were moderately high (P= 57.10%, A= 0.7857, Ap= 0.60714 and H = 0.1542) compared to E T. aureoviride and T. longibrachiatum. The genetic variation attributable to differences among populations was 7.857%. The mean gene flow among populations was Nm = 1.3351. Genetic identities (I) ranged from 0.9397 to 0.9642 with a mean of 0.94846. Outcrossing rates based on fixation indices average (t) was 0.2334. Nevertheless, the alleles for α-EST-b showed a very low frequency of 0.0400. The polymorphic locus of MDH1 was of the fast allele of T. harzianum, MD1-a, was prevalent in T. aureoviride and T. longibrachiatum populations. Using a UPGMA cluster analysis, T. harzianum and T. longibrachiatum populations were totally separated in these cluster except T. aureoviride populations. T. harzianum presents high levels of genetic diversity compared with other Trichoderma species.